MENGENAL KONSEP ONTOLOGI, EPISTEMOLOGI DAN AKSIOLOGI DALAM ILMU EKONOMI ISLAM: UNDERSTANDING THE CONCEPTS OF ONTOLOGY, EPISTEMOLOGY AND AXIOLOGY IN ISLAMIC ECONOMICS - Shovia Indah Firdiyanti Firdiyanti; Siti Mudrikah Mudrikah; Muhammad Sulthon Sulthon (Universitas Wahid Hasyim Semarang, 2025)
This study is motivated by the increasing popularity of Islamic economics in Indonesia as Muslim awareness of applying Islamic law grows, particularly in the economic sector. This study aims to critically analyze the philosophical concepts of science—including ontology, epistemology, and axiology—within the framework of Islamic economics. Using a qualitative approach and descriptive analysis methods, this study examines the philosophical foundations that distinguish Islamic economics from conventional economic systems. The findings of this study indicate that, ontologically, Islamic economics not only studies human economic activities such as production, consumption, and distribution, but also integrates them as an integral part of worship and devotion to Allah SWT. Epistemologically, knowledge in Islamic economics is built through the integration of revelation (naqli) and reason (aqli), using deductive and inductive methods derived from the Quran, hadith, as well as empirical observation and rationality. Meanwhile, from an axiological perspective, religious values and ethics serve as the main pillars guiding the objectives of Islamic economics toward public welfare and social justice. The novelty of this research lies in the systematic conceptual mapping of the philosophy of science in Islamic economics, which has not been thoroughly examined in contemporary philosophical studies. The theoretical contribution of this study is the strengthening of the scientific foundation of Islamic economics as an independent and transformative discipline rooted in divine values. The practical contribution is to provide a conceptual framework that can be used by academics, researchers, and policymakers in developing an Islamic economic system that is more value-oriented and sustainable. Thus, this research serves as the initial foundation for strengthening the paradigm of Islamic economics based on the philosophy of science.